BRACAVENIR - impact of a psychoeducational intervention on expectations and coping in young women (aged 18–30 years) exposed to a high familial breast/ovarian cancer risk: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Kwiatkowski, Fabrice; Dessenne, Pascal; Laquet, Claire; Daures, Jean-Pierre; Gay-Bellile, Mathilde; Bignon, Yves-Jean
Abstract Background Young women exposed to a high hereditary breast and ovarian cancer (HBOC) risk are particularly vulnerable. They are ignored by health prevention measures but exposed to a stream of contradictory information (medicine, media, Internet). They may feel concerned about surgical prevention issues at a key moment of their identity construction (self, relationship, sexuality). We designed a special psychoeducational intervention to help these women cope better with these difficulties. Methods/design The BRACAVENIR study consists of a prospective, randomized superiority phase II trial with a wait list control group. Participants are childless young female counselees (aged 18–30 years) seen at the oncogenetics department of the Centre Jean Perrin and belonging to HBOC families either with or withoutBRCA mutations. They will be invited to attend a weekend group session at a spa resort and to participate in short expert conferences and focus group activities (group sharing, Moreno role game) supervised by a psychotherapist. Two sessions separated by a 6-month delay (wait list) will enable us to evaluate the intervention's effect by comparing questionnaire scores between the 6-month time points. The main endpoint is an increase of the Herth Hope Index by at least 1 SD. Secondary endpoints are self-esteem, anxiety trait, anxiety state, coping, and quality of life. With a one-sided α = 0.05 and β = 0.20, 12 participants will be needed by group, plus an additional 2 in anticipation of dropouts. Participants will be randomized 1:1 to the first or the second session so that the groups will be comparable. Discussion The intent of this trial is to bridge the gap on a psychosocial level in these young women with HBOC. A particularity of the design is the use of a waiting list, which should allow for avoiding major bias. The intervention consists of a short session that could be proposed to other young counselees if successful. The results may bring complementary information to facilitate the intervention and also influence the contents of the oncogenetic consultation. Trial registration Ethics committee CPP SUD-EST-6: IRB00008526. Registered on 18 March 2016. ClinicalTrials.gov identifier:NCT02705924 . Registered on 2 March 2016.